Metformin inhibits melanin synthesis and melanosome transfer through the cAMP pathway - Xing Liu; Xiaojie Sun; Yunyao Liu; Wenzhu Wang; Hedan Yang; Yiping Ge; Yin Yang; Xu Chen; Tong Lin (Scientific Reports)
Abstract Several studies have demonstrated the inhibitory effect of metformin on pigmentation. However, the effect of metformin on melanosome transfer remains unknown. The goals of this study were to elucidate the effects of metformin on melanogenesis and melanosome transfer and explore the related mechanisms. We determined that, compared with those in the control zebrafish, the area occupied by pigment granules, melanin content, tyrosinase activity, and the expression levels of melanogenesis genes and melanosome transfer-related genes were reduced in metformin-treated zebrafish. In human primary melanocytes, MNT1 cells/B16F10 cells, metformin also plays a negative role in melanin synthesis regardless of health status and α-MSH-induced pigmentation. Unlike arbutin, metformin inhibited the formation of dendrites and filopodia-like structures and suppressed melanosome transfer. After treatment with metformin, the cAMP content was reduced, the expression of MITF and downstream molecules was downregulated, and the expression of Rho GTPases was changed. Metformin partially abrogated the changes in genes regulating melanin synthesis, melanosome transfer and the cytoskeleton induced by a cAMP activator. Furthermore, the Nrf2 expression was decreased upon metformin intervention, and metformin partially abrogated the changes in genes regulating melanogenesis caused by a Nrf2 activator. Our study revealed that metformin can serve as a candidate depigmentation agent.